Designing Blended Learning Materials for Functional Texts in Fiction Study - Ulyati Retno Sari - (ELITE Association Indonesia, 2020)
In fiction study traditional class is complicated. It always challenges to teach students fiction. They do not appreciate literature pieces as much as teacher used to in those good old days. It notices that students these days do not read many literature pieces or getting students to read the text before class. This happens also in Elements of Prose class in English Department at UIN Sunan Kalijaga. One solution to this problem that is discussed in this study is mixed method between face to face-classroom with online learning that is called blended learning. Blended learning goes beyond barriers of time, location, and culture and has created many enhanced opportunities for learners and instructors. It is effective because it allows students to read e-book versions and in classroom time, they are more focus and active on meaningful activities related with their learning materials.